2018
DOI: 10.1002/qj.3206
|View full text |Cite
|
Sign up to set email alerts
|

Comparing ECMWF high‐resolution analyses with lidar temperature measurements in the middle atmosphere

Abstract: Middle atmospheric lidar temperature observations conducted above Sodankylä, Finland (67.4°N, 26.6°E), during December 2015 are compared with two estimates of the atmospheric state computed by the integrated forecast system (IFS) of the European Centre for Medium‐Range Weather Forecasts (ECMWF). The first set corresponds to an hourly sampling of the middle atmosphere by high‐resolution analyses and very short‐range forecasts produced by the operational IFS cycle 41r1 at a horizontal resolution of 16 km. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 29 publications
7
58
0
Order By: Relevance
“…The horizontal resolution of the IFS cycle used for this study is about 9 km (Hólm et al, ; Malardel & Wedi, ). Ehard et al () analyzed ground‐based lidar measurements from December 2015 and showed that the IFS data give reliable gravity wave amplitudes up to about 40‐ to 50‐km altitude. During the same period, the phase and location of mountain wave‐induced polar stratospheric clouds above Svalbard was very well simulated (Dörnbrack et al, ).…”
Section: Observed Mountain Wavementioning
confidence: 99%
“…The horizontal resolution of the IFS cycle used for this study is about 9 km (Hólm et al, ; Malardel & Wedi, ). Ehard et al () analyzed ground‐based lidar measurements from December 2015 and showed that the IFS data give reliable gravity wave amplitudes up to about 40‐ to 50‐km altitude. During the same period, the phase and location of mountain wave‐induced polar stratospheric clouds above Svalbard was very well simulated (Dörnbrack et al, ).…”
Section: Observed Mountain Wavementioning
confidence: 99%
“…before and during the regime transition. As shown by Le Pichon et al (2015) or Ehard et al (2018), IFS analyses are a reliable indicator of stratospheric gravity wave activity up to about 45 km altitude. Especially, the most recent increase of the IFS horizontal resolution is able to reproduce realistic gravity wave amplitudes in the lower and middle 15 stratosphere (Dörnbrack et al, 2017a).…”
Section: Discussion and Summarymentioning
confidence: 97%
“…The IFS cycle 41r2 was in its preoperational mode and products were disseminated among the users. Ehard et al (2018) showed that both IFS cycles reproduce the temporal evolution of the observed gravity wave potential energy density E P in the middle stratosphere above 5 Sodankylä, Finland correctly for the months December 2015 to March 2016. Therefore, the IFS cycle 41r2 was selected for the present analysis and profiles of the IFS cycle 41r1 are only shown for comparison in Figure 3.…”
Section: Meteorological Data From the Ifs 25mentioning
confidence: 88%
“…Gravity waves in the MLT can be inferred from these measurements by observing patterns in either airglow volume emission, odd oxygen, or temperature. Among these, analysing gravity waves in the temperature field is most beneficial as temperature is directly connected to the basic state of the atmosphere and as gravity wave momentum flux becomes accessible (Ern et al, 2004). To this end, temperature amplitudes as well as horizontal and vertical wavelengths need to be inferred from the measurements.…”
Section: Measurement Conceptsmentioning
confidence: 99%
“…All of these data fields can serve as input to an analysis of gravity waves and other atmospheric structures. However, there is a particular interest in wave retrievals from the temperature field as it allows for the analysis in terms gravity wave momentum flux (GWMF), potential energy density, and other quantitative wave properties (Ern et al, 2004;Fritts et al, 2014). The gravity wave retrieval involves several steps.…”
Section: Retrieval Of Gravity Wavesmentioning
confidence: 99%